Analyzing animal movement patterns using potential functions. Issue 3 (4th March 2013) - Preisler, Haiganoush K.; Ager, Alan A.; Wisdom, Michael J.
Abstract : The advent of GPS technology has made it possible to study human‐wildlife interactions on large landscapes and quantify behavioral responses to recreation and other anthropogenic disturbances at increasingly fine scales. Of particular interest are the potential impacts on habitat use patterns, energetics, and cascading impacts on fecundity and other life history traits for key wildlife species that are exposed to human activities. Statistical models quantifying effects of human activity on animal movement on a heterogeneous landscape are essential for understanding these potential impacts. Here we present a statistical framework for analyzing movement data that is based on the concept of a potential surface. The potential surface is motivated by the assumption that animals are moving on a space‐time surface with regions or points of attraction or of repulsion. We demonstrate the use of the technique by analyzing movement data from a long‐term controlled experiment to evaluate the responses of free ranging Rocky Mountain elk ( Cervus elaphus ) to anthropogenic disturbances that vary in time and space. Our results demonstrated a strong avoidance of elk to all‐terrain vehicles detected up to one km from the disturbance. Elk avoidance of mountain bikers was detected up to 500 m, and avoidance of hikers and horseback riders was detected to 200 m.